Comparison of hepatic arterial infusion chemotherapy between 5‐fluorouracil‐based continuous infusion chemotherapy and low‐dose cisplatin monotherapy for advanced hepatocellular carcinoma. Issue 13 (23rd August 2018) - Kawaoka, Tomokazu; Aikata, Hiroshi; Kobayashi, Tomoki; Uchikawa, Shinsuke; Ohya, Kazuki; Kodama, Kenichiro; Nishida, Yuno; Daijo, Kana; Osawa, Mitsutaka; Teraoka, Yuji; Inagaki, Yuki; Honda, Fumi; et al.
Abstract : Aim: The aim of this study is to compare the efficacy and safety of hepatic arterial infusion chemotherapy (HAIC) between 5‐fluorouracil (5‐FU)‐based continuous infusion chemotherapy and low‐dose cisplatin (CDDP) monotherapy in patients with advanced hepatocellular carcinoma (HCC). Methods: Patients were grouped according to HAIC regimen (5‐FU group, n  = 317/CDDP group, n  = 66). A two‐to‐one match was created using propensity score analysis (5‐FU group, n  = 102/CDDP group, n  = 51). After matching, response rate (RR) and adverse events as primary end‐points, and survival and progression‐free survival as secondary end‐points, were analyzed. Results: In the analysis of primary end‐points, the RR in the 5‐FU group was significantly higher than in the CDDP group (32.4% vs. 15.7%, P  = 0.033). In patients with a Child–Pugh (CP) score of 5–7, the RR in the 5‐FU group was significantly higher than that in the CDDP group (36.1% vs. 15.4%, P  = 0.020). In those with a CP score of 8–9, there was no significant difference in RR between the two groups (15.8% vs. 16.6%, P  = 1.000). The reservoir system‐related complications were 9.8% in the 5‐FU group, and there was no significant difference in the incidence of grade 3/4 adverse events between the two matched groups ( P  > 0.05). In terms of secondary end‐points, the median survival time was 9.1 and 8.7 months for the 5‐FU and CDDP groups, respectively ( P  = 0.4917). Progression‐free survival was 3.9 months for the 5‐FU group and 4.9 months for the CDDP group ( P  = 0.4). Conclusions: 5‐Fluorouracil‐based continuous infusion chemotherapy could be suitable for advanced HCC patients with a CP score of 5–7 considering the treatment response.